Sorption of lead from aqueous system using cocoa pod husk biochar: kinetic and isotherm studies - Kong Yong, Soon; Leyom, Jesielyna; Chay Tay, Chia; Abdul Talib, Suhaimi (International Journal of Engineering and Technology, 2018)
Cocoa pod husk (CPH) was pyrolyzed at 500Â°C to produce biochar (CPHB) for sorption of lead (Pb) from aqueous system. Chemical characterization for CPHB was conducted using Fourier transform infrared (FTIR) spectroscopy, Boehm titration and X-ray fluorescence (XRF) spectroscopy. Sorption parameters for CPHB (i.e., sorbent dosage, pH, contact time, and Pb concentration) were optimized. Elemental compositions for CPHB are C (66% w/w), O (19% w/w), and N (2% w/w). The ash of CPHB consists of calcium oxide (CaO) (4.6% w/w) and potassium oxide (K2O) (4.2% w/w), with negligible amount of heavy metals (1% w/w). Upon treatment with artificial Pb wastewater, FTIR spectra for CPHB revealed shifting of nasymm(COO-) and nsymm(COO-) bands from 1560 cm-1 to 1575 cm-1 and 1416 cm-1 to 1398 cm-1, respectively. The optimum sorption parameters were determined (i.e., sorbent dosage: 1.0 g/L; pH 5; input Pb concentration; 50 mg/L; and sorption time: 210 minutes). Sorption of Pb by CPHB was best described by pseudo-second-order kinetic model (R2= 0.835), and Langmuir isotherm model (R2= 0.962). Maximum Langmuir Pb sorption capacity for CPHB (qmax) was 69.9 mg/g. These findings suggested that the sorption of Pb by CPHB may have occurred through (1) coordination with polar groups (i.e., carboxylate and phenolate) and (2) precipitation with alkaline materials (i.e., CaO and K2O).Â Â